2010
DOI: 10.1089/apc.2009.0328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficiency of Patient Flow at Three HIV Clinics in Uganda

Abstract: With dramatic increases in antiretroviral therapy (ART) provision, many clinics in sub-Saharan Africa are congested, but little attention has focused on the efficiency of clinics. Between April and June 2008, we conducted a time-and-motion study to assess patient flow at three HIV clinics in Uganda. Mulago HIV Clinic had 6,700 active patients, compared with 2,700 at Mbarara Municipal Council Clinic (MMC) and 2,800 at Reachout Mbuya (ROM). Mulago had six doctors and eight nurses; MMC had two doctors and two nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 11 publications
3
41
3
Order By: Relevance
“…The added responsibility of child care, need for employment, fear of disclosure, and abandonment have been proposed as contributing factors. 17-21 Yet in our study, we did not find these to be predictive factors of optimal retention. For example, 63% of women in our study population reported 2 or more children at home; however, this was not a predictor of optimal retention.…”
Section: Discussioncontrasting
confidence: 92%
“…The added responsibility of child care, need for employment, fear of disclosure, and abandonment have been proposed as contributing factors. 17-21 Yet in our study, we did not find these to be predictive factors of optimal retention. For example, 63% of women in our study population reported 2 or more children at home; however, this was not a predictor of optimal retention.…”
Section: Discussioncontrasting
confidence: 92%
“…The evidence is mixed. Wanyenze et al 3 found that wait times in nurse managed clinics were significantly longer than those in physician managed clinics while two contradictory studies found that task shifting resulted in a decrease in mean wait time. 4,5 O'Brien et al measured the effect that task shifting has on physicians' workload in Rwanda on the assumption that a reduced workload would allow physicians to redirect their time to enrolling patients.…”
Section: Wait Times and Workforcementioning
confidence: 99%
“…For example, structural barriers such as transportation and opportunity costs of obtaining "free" care can be high, especially in rural settings [2]. Overcrowded clinics and long waiting times are delivery barriers that can create an unwelcoming environment for patients seeking care [3,4]. Stigma and depression remain important psychosocial barriers [5].…”
Section: Introductionmentioning
confidence: 99%